RELEVANSI POLA PENDIDIKAN RASULULLAH DALAM MENJAWAB TANTANGAN PENDIDIKAN ISLAM ABAD 21 - Wijayanti, Rizki; Adibah, Ida Zahara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to conceptually analyze the educational pattern of the Prophet Muhammad (PBUH) and formulate its relevance as a transformative strategy in addressing the challenges of Islamic education in the 21st century. In the current era of digital disruption, Islamic educational institutions face complex challenges, including moral degradation in cyberspace, identity polarization, and shifts in religious authority. This research employs a qualitative approach using a library research method. Primary data sources are derived from authoritative Sirah Nabawiyah literature. The findings reveal that the Prophet’s educational pattern, which is based on uswah hasanah (exemplary conduct), dialogical pedagogy (hiwar), and the principle of tabayyun (verification), constitutes a crucial foundation for the development of ethical digital literacy. This article proposes a “Prophetic-Digital Pedagogy” model that integrates prophetic values into the modern learning ecosystem. The study concludes that the revitalization of classical educational methods is not merely a form of historical romanticism, but an urgent necessity for building the moral and intellectual resilience of future learners.